2012
DOI: 10.1177/1757913912444850
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinations and preventive screening services for older adults: opportunities and challenges in the USA

Abstract: Vaccinations and disease-screening services occupy an important position within the constellation of interventions designed to prevent, forestall or mitigate illness: they straddle the worlds of clinical medicine and public health. This paper focuses on a set of clinical preventive services that are recommended in the USA for adults aged 65 and older, based on their age and gender. These services include immunisations against influenza and pneumococcal disease, and screening for colorectal and breast cancers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…11 In contrast, using a set of select clinical preventive services recommended by age and gender, about 26% of adults aged 50–64 years in 2009 were up-to-date on select services compared to about 48% of older adults. 24,25 Additionally, a study by Lima et al 26 found that adults aged 52–62 years with functional limitations were cared for primarily by spouses, the majority remained in the workforce and typically provided fewer hours of care as compared to that received by older age groups. Moreover, those in midlife, particularly women, are also more likely to be responsible for caring for both dependent adult children as well as older family members, which has serious implications for prevention.…”
Section: A Life-course Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…11 In contrast, using a set of select clinical preventive services recommended by age and gender, about 26% of adults aged 50–64 years in 2009 were up-to-date on select services compared to about 48% of older adults. 24,25 Additionally, a study by Lima et al 26 found that adults aged 52–62 years with functional limitations were cared for primarily by spouses, the majority remained in the workforce and typically provided fewer hours of care as compared to that received by older age groups. Moreover, those in midlife, particularly women, are also more likely to be responsible for caring for both dependent adult children as well as older family members, which has serious implications for prevention.…”
Section: A Life-course Perspectivementioning
confidence: 99%
“…25 In line with Healthy People 2020 targets, 35 a number of indicators for monitoring the use of clinical preventive services among adults aged 50–64 years have been identified, including a set of screening services and risk factors related to cancer detection and prevention. 24 Cancer prevention guidelines often include the recommended clinical preventive services (including colorectal cancer screening, mammography, and Pap tests) and also promote a reduction in cancer risk factors such as physical inactivity, smoking, alcohol consumption, and obesity.…”
Section: Life-course Approach To Cancer Preventionmentioning
confidence: 99%
“…2 To combat these high risks in the elderly, the 10-year goal of Healthy People 2020 is to increase adult-vaccination rates of persons 65 years and older by 10%. 7 Of those who develop Hz, 10%-25% will develop peripheral herpetic neuralgia (PHN); the occurrence of PHN is 3 times higher in people 65 years or older. 8 This condition is the most prevalent, painful, and long-lasting complication of Hz, consisting of severe neuropathic pain, with only palliative treatment available.…”
Section: Descriptionmentioning
confidence: 99%
“…This project was also influenced by the Healthy People 2020 initiative that recognized low adult vaccination rates and set a goal to increase vaccinations in adults by 10%. 7 The live attenuated Hz vaccine can reduce the incidence of a shingles outbreak by 70% in ages 50 to 59, 64% in ages 60 to 69 and 38% in ages 70 years and older. 4 Additionally, the Hz vaccine reduces the occurrence of PHN by 66% in ages 60 years and older.…”
Section: Descriptionmentioning
confidence: 99%
See 1 more Smart Citation